FRI0387 DISEASE COURSE AND OUTCOMES DURING PREGNANCY IN PATIENTS WITH AXIAL SPONDILOARTHRITIS: COMPARISON BETWEEN TNFI USERS AND NAIVE PATIENTS. (June 2019) - Crisafulli, Francesca; Andreoli, Laura; Gerardi, Maria Chiara; Fernández, Antía García; Nalli, Cecilia; Filippini, Matteo; Gorla, Roberto; Taglietti, Marco; Fredi, Micaela; Lazzaroni, Maria Grazia; Lojacono, Andrea; Zatti, Sonia; et al.
Abstract : Background: Axial Spondiloarthrtis (AxSpA) can be active during pregnancy, especially in those patients who discontinued TNFi at the beginning of pregnancy. The severity of flare during pregnancy can influence the gestational outcome and the attitude of the physician towards treatment. Objectives: To describe: 1)the disease course of AxSpA during pregnancies in patients who never used TNFi (bio-naïve) and those who were TNFi users; 2)the severity of flares; 3)the impact of resuming TNFi in patients who experienced a flare during pregnancy (on both maternal disease control and gestational outcome). Methods: Retrospective analysis of 18 prospectively-followed pregnancies from 2010 to 2018 in 15 patients with AxSpA. Two pregnancies ended in miscarriage, so they weren't considered for the analysis of flares during pregnancy. Active disease was defined as ASDAS-CRP >2.1. Flare was defined as an increase of ASDAS-CRP greater than 0.6 with CRP elevation and one of the followings: introduction or increase above 5mg/day of prednisone, introduction of cDMARD or bDMARD. Results: At preconception visit, 2 patients were on treatment only with steroids, 1 with sulfasalazine and steroids and 9 with bDMARDs (5 etanercept, 2 adalimumab, 2 golimumab; 2 with steroids). At conception, 3 patients presented active disease. TNFi was stopped at positive pregnancy test in 7 pregnancies; 1 patient continued TNFi over pregnancy. Twelve out of 16 (75%) patients had at least one disease flare (4, 10 and 3 during 1 st, 2 nd and 3 rd trimester respectively). Among pregnancies with flare, medication resumed during pregnancy were steroids (7, 58%), cDMARDs (1 salazopyrine and 1 cyclosporine A, 17%) and bDMARDs (4 etanercept and 1 certolizumab, 42%). Six patients (38%) had a flare in postpartum period. Table 1 shows the comparison between pregnancies with and without flares during pregnancy. By comparing the pregnancies of patients with and without history of TNFi use (table 2), we have registered 8 flares (8/11, 73%) in the first group and 4 flare (4/5, 80%) in the second one. In the group of TNFi users, medications resumed during pregnancy were steroids in 5/11 (46%) and bDMARDs in 5/11 (46%), whereas in the group TNFi naïve only in 1 pregnancy steroids was resumed and no bDMARDs were started. Mean ASDAS-CRP was higher in the group of TNF user. For what concerned gestational outcome, we did not observe any SGA, pre-eclampsia and eclampsia. Two pregnancies ended with miscarriage and 2 with preterm birth (at 36 and 34 gestational weeks). Two patients had PROM and 1 pPROM (this patient refused to resume TNFi during pregnancy and her flare was treated with medium doses of prednisone). Conclusion: Three out of 4 AxSpA patients with severe disease phenotype and history of TNFi use prior to pregnancy experienced a disease flare after TNFi discontinuation at conception. Conversely, AxSpA patients with mild disease phenotype had a similar rate of flare during pregnancy but less severe and without the need for chronic treatment during pregnancy. When resumed during pregnancy TNFi was able to control disease activity and to favor a good gestational outcome. In preconception counselling the continuation of TNFi during pregnancy should be discussed with the patients. Disclosure of Interests: Francesca Crisafulli: None declared, Laura Andreoli: None declared, Maria Chiara Gerardi: None declared, Antía García Fernández: None declared, Cecilia Nalli: None declared, Matteo Filippini: None declared, Roberto Gorla: None declared, Marco Taglietti: None declared, Micaela Fredi: None declared, Maria Grazia Lazzaroni: None declared, Andrea Lojacono: None declared, Sonia Zatti: None declared, Franco Franceschini: None declared, Angela Tincani Consultant for: UCB, Pfizer, Abbvie, BMS, Sanofi, Roche, GSK, AlphaSigma, Lillly, Jannsen, Cellgene, Novartis